Association between Advanced Lung Cancer Inflammation Index and 30-day mortality in patients with spontaneous intracerebral hemorrhage: a retrospective cohort study - Ding, Jianzhong; Zhang, Jiquan; Lv, Wanqiu; Xiao, Yangchun; Fang, Fang; Ma, Wenchao; Zhang, Yu; Zhong, Xiaoli (Frontiers in Neurology, 2025)
Background and purposeSpontaneous intracerebral hemorrhage (ICH) is a leading cause of stroke-related mortality, with early outcomes significantly influenced by inflammation and malnutrition. However, the prognostic value of composite biomarkers, which integrate multiple factors such as inflammation and nutritional status, remains insufficiently explored, particularly in the context of early outcomes following ICH. This study explores the association between the Advanced Lung Cancer Inflammation Index (ALI) and 30-day mortality in ICH patients, evaluating its prognostic value as a composite biomarker that integrates body mass index (BMI), serum albumin, and neutrophil-to-lymphocyte ratio (NLR).MethodsA retrospective cohort study was conducted on 2,459 ICH patients from a single institution, West China Hospital, between January 2009 and June 2019. ALI was calculated using the formula ALI = (BMI × Alb)/NLR, and patients were stratified into quartiles based on ALI scores. The primary outcome was 30-day mortality, and logistic regression analysis was employed to evaluate the association between ALI and mortality.ResultsThe 30-day mortality rate was 23.3% (n = 574) in the cohort, with higher ALI scores significantly correlating with lower mortality. Patients in the highest ALI quartile (Q4) had 55% lower odds of mortality compared to those in the lowest quartile (Q1) (adjusted odds ratio [AOR]: 0.45, 95% CI: 0.31–0.63, p < 0.001). Each 1-standard deviation increase in ALI (as a continuous variable) was associated with a 5% reduction in mortality odds (AOR: 0.95, 95% CI: 0.93–0.96, p < 0.001). ROC curve analysis demonstrated that ALI outperformed individual biomarkers (BMI, albumin, and NLR) in predicting mortality, with an AUC of 0.681, which further improved to 0.811 when ALI was integrated into the ICH prediction model.ConclusionALI is a reliable composite biomarker, with higher ALI scores being significantly associated with reduced 30-day mortality in patients with ICH.